TREATMENT OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) SEPSIS WITH COMBINATION OF FOSFOMYCIN AND AMIKACIN IN A PATIENT WITH SCALD-BURN INJURY - Putra, Oki Nugraha; Saputro, Iswinarno Doso; F, Ana Khusnul (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Thus, this case report assesses the efficacy combination of fosfomycin and amikacin in the management of MRSA infection in a burn patient. Case Report: A 31-year-old male was transferred to the burn center for definitive treatment. Initially, the patient was treated with ceftazidime injection as empiric antibiotic one gram three times daily, but the patient became sepsis during the treatment. Blood specimen was taken and Methicilin Resistant Staphylococcus aureus (MRSA) was isolated from this culture. The patient was isolated and based on antibiotic susceptibility, the patient was started on fosfomycin 2 gram IV twice daily for first seven days, and after that fosfomycin was combined with amikacin IV 500 mg once daily. After administration of these antibiotics, a rapid clinical improvement was observed with the patient, leucocytosis did not occur and blood culture was negative. The patient completed a total of 14 days of fosfomycin and 8 days of amikacin therapy. Conclusion: The synergistic combination of fosfomycin with amikacin, may be useful alternative treatment option for sepsis related Methicilin- Resistant Staphylococcus aureus (MRSA) in burn injury. Further research is also needed to clarify effectiveness of fosfomycin and amikacin to treat MRSA infection in burn patient.